Pengaruh Profesionalisme dan Akuntabilitas terhadap Kualitas Audit (Studi Literature Review) - Dimas Prayudha Anggoro; Sjarief Hidajat (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The objective of this study is to examine how auditor professionalism and accountability impact audit quality through a literature review employing a qualitative methodology. Data were gathered from five national journals sourced from Google Scholar and scrutinized for data processing. The analytical process aimed to derive conclusions from the test outcomes to assess the influence of professionalism and accountability on audit quality. In general, most research findings support a positive correlation between auditor professionalism and audit quality, though several studies suggest variations indicating that professionalism may not consistently enhance audit quality. It is widely recognized that accountability generally contributes positively to audit quality, despite discrepancies found in certain studies.